Children's stories in dual language French & English : raise your child to be bilingual in French and English - Bibard, Frederic (Talk in French, 2020)
Boost your child's reading and listening skills in English and French with this bedtime stories collection plus downloadable audio. Now you can introduce your child to the joys of reading and bond with them before bedtime while learning a second language. What you get with the Children's Stories in Dual Language French & English: 10 fantasy stories for kids: Get your kids excited about bedtime by reading magical short stories together for children ages 7-12. Parallel English and French text: Read the specially designed stories either in English or in French and learn new vocabulary in both languages. Raise your child to become bilingual: This bilingual storybook is a perfect way to get your child interested in learning a second language. French and English audio: The book comes with downloadable audio in both French and English. Follow along as you read or listen to the audio together with your child. Great for adults, too! For French language learners who love short fantasy stories, this book will help you learn vocabulary and improve your listening and pronunciation skills in an effortless and enjoyable way. Make tonight's bedtime routine fun and exciting with this book and its accompanying audio!